Penerapan Modifikasi Psikoedukasi Pada Penderita Diabetes Mellitus Tipe2 - Huzaimah, Nailiy (Universitas Tribhuwana Tunggadewi, 2018)
Controlled blood glucose level is one of the success indicator of the diabetes management. A good comprehension, high self-efficacy, and good family support is needed to encourage and strengthen the effort of individuals to achieved good behavioral diabetes self-management, which helped to control blood glucose level. This study aimed to determine the Psychoeducation Modification’s effects on comprehension, self-efficacy, family support, behavioral diabetes self-management, and blood glucose level of people with type 2 diabetes mellitus (T2DM). This study used pre and post test control group design. Respondents of this research are population with T2DM and their families who are undergoing outpatient treatment at Internal Medicine Outpatient Unit of Dr. H. Moh. Anwar Sumenep Hospital (n = 40). Collecting data included the patients comprehension, self-efficacy, behavioral self-management of diabetes, family support, and random blood glucose level. Data collection used questionnaires and the laboratory test of blood glucose level, then analyzed by a different test with the α value